Integrated Marketing Communication To Increase Brand Equity In Clove Garden Hotel and Residence - Diah Armita, Sendika; Wandebori, Harimukti (Journal of Business and Management, 2019)
In this present time, the rapid growth of hotel industry especially in Bandung makes a major competition between the business people. Clove Garden Hotel and Residence is one of the hotels in Bandung that located in Jalan Awiligar Raya II. A major difficulty of hotel industry because the growths of hotel in Bandung are a lot but the number of visitors that came to Bandung is decrease, it causes the unoccupied rooms in Clove Garden Hotel and Residence. Advancement to get information about Clove Garden Hotel and Residence are needed to increase the brand equity through the effectiveness of all media in integrated marketing communication that implemented by Clove Garden Hotel and Residence in an attempt to increase sales. The author concluded that the purpose of this research which are to identify current integrated marketing communication that implemented by Clove Garden Hotel and Residence, to identify current external and internal factor in Clove Garden Hotel and Residence and learn how integrated marketing communication contribute to brand equity. This research applied a qualitative and quantitative method. The qualitative method is the result of interview that has been done with Clove Garden Hotel and Residence’s staffs to analyze the external and internal current condition marketing strategy that applied there. Meanwhile, the quantitative method through offline and online questionnaire with the total of 100 respondents with the criteria whether people who knows about Clove Garden Hotel and Residence or customer that has been stayed in Clove Garden Hotel and Residence. After that, the relation between integrated marketing communication and brand equity will be analyzed using multiple linear regressions from SPSS software to analyze what variable in integrated marketing communication that gives significant effects to brand equity.The analysis result shows that Clove Garden Hotel and Residence has implemented all of integrated marketing communication and effect brand equity significantly. Meanwhile, the result shows that direct and database marketing is the most effective media that gives and effect towards brand equity, followed by public relation, online and social media, mobile marketing, advertising, personal selling, sales promotion and the least is event.